Correction: The role of stickiness in the rheology of semiflexible polymers. Issue 40 (2nd October 2019) - Golde, Tom; Glaser, Martin; Tutmarc, Cary; Elbalasy, Iman; Huster, Constantin; Busteros, Gaizka; Smith, David M.; Herrmann, Harald; Käs, Josef A.; Schnauß, Jörg
Abstract : Correction for 'The role of stickiness in the rheology of semiflexible polymers' by Tom Golde et al., Soft Matter, 2019, 15, 4865–4872.